Severity of asthma: the role of CD25+,CD30+, NF-κB, and apoptotic markers - Abdulamir, Ahmed Sahib; Kadhim, Haider Sabah; Hafidh, Rand Riadh; Ali, M. A.; Faik, I.; Abu Bakar, Fatimah; Abbas, Kassim Ali (Esmon Publicidad, 2009)
Objectives: We studied the role of the regulatory T cells CD4+CD25+ (Treg) and activated CD4+CD30+ cells in the pathogenesis of asthma and their association with apoptosis and NF-κB in patients with mild intermittent asthma (MA), severe persistent asthma (SA), and healthy volunteers (HV). Methods: Peripheral blood lymphocytes (PBL) were extracted from asthmatic patients during exacerbations, and CD4+ cells were separated using Dynal beads. Immunostaining of whole PBL for NF-κB, Bax, and Bcl-2, and immunostaining of CD4+ cells for CD25+ and CD30+ cells were performed using immunocytochemistry. Results: Treg cells were expressed at higher levels in MA than in HV and SA (P<.05), while CD30+ T cells were expressed at higher levels in both SA and MA than in HV (P<.05), although there was no remarkable difference between SA and MA (P>.05). Levels of NF-κB, Bcl-2, and Bcl-2/Bax increased, whereas those of Bax decreased, progressively, from MA to SA (P<.05). NF-κB levels correlated directly with the Bcl-2/Bax ratio and with CD4+CD30+ cells in SA and MA, whereas CD4+CD30+ cells correlated inversely with the Bcl-2/Bax ratio. Conclusions: Unregulated Treg cells probably return inflammatory responses to normal values during exacerbations in MA; however, expression of Treg cells was extensively diminished in SA, leading to probable loss of suppressive control over underlying immune reactions. CD4+CD30+ cells were associated with the pathogenesis of asthma but not with severity. NF-κB seems to be the central inflammatory factor in SA, with a remarkable loss of PBL apoptosis, diminished Treg levels, and high CD30+ cell levels that probably induce NF-κB, which in turn blocks the proapoptotic potential of CD30 induction itself.